History and memory in the Abbasid Caliphate - Osti, Letizia. (London)
xii, [1] sayfa harita, 183 sayfa
Keywords: “Abu Bakr al-Suli was an Abbasid polymath and table companion, as well as a legendary chess player. He was perhaps best known for his work on poetry and chancery, which would have a long-lasting influence on Arabic literature. His decades of service at the court of at least three caliphs give him a unique perspective as an historian of his own time, although he is often valued as an observer rather than an interpreter of events for posterity. Letizia Osti here provides the first full-length English-language study devoted to al-Suli, illustrating how investigating the life, times and works of such a complex individual can serve as a fil rouge for tackling broader, contested concepts, such as biography, autobiography, court culture, and written culture. The result is an exploration of the ways in which the Abbasid court made sense of the past and, in general, of what 'historiography' means in a medieval Arabic context“ -- Yayıncı.